Endoscopic removal technique of migrated pancreatic plastic stents. (17th February 2014) - Matsumoto, Kazuyuki; Katanuma, Akio; Maguchi, Hiroyuki
Abstract Endoscopic pancreatic stenting (EPS) is used for various pancreatic conditions. With the increasing use of pancreatic stents, many complications have been observed. Especially, proximal stent migration presents a more serious condition because of the possibility of pancreatic duct (PD) damage. However, the removal of proximally migrated stents is technically challenging because of the small PD diameter, the bended PD course, the presence of PD strictures, and the lack of suitable devices for stent removal. Thus, few cases of surgical intervention have been encountered. In this study, we review the endoscopic treatment of proximally migrated pancreatic plastic stents. We classify migrated stent conditions into four types according to stent and PD conditions. In Type A, the main pancreatic duct (MPD) has no stricture. In Type B, the stent is positioned across the stricture on the MPD. In Type C, the stent is positioned further away from the stricture on the MPD. The tip of the proximal stent is located in the MPD in types A thru C. In Type D, the tip of the proximal stent is located in a branch duct. We introduced the strategy of endoscopic removal technique of each type of migrated plastic stents.